Acetic acid Effect on Seedling Growth of Some Anoxia-tolerant Land Race Rice (Oryza sativa L) Genotypes (The Agriculturists, 2010)
An in vitro study was conducted to observe the effect of acetic acid in the process of seedling growth of five anoxia-tolerant land race rice genotypes (Tepi boro, Chaita boro, Bashful, Jahmir and Banajira) under hypoxic condition at two pH levels: pH 5 and pH 7. The acetic acid concentrations were 0, 4, 8 and 12 mM. Seedlings were grown in the test tubes containing 18 ml acetic acid-water solution (equivalent to 50 mm water column above the seed) under the two pH conditions at 30 °C for 7 days in dark. The nature and extent of the genotype responses varied with the concentrations of acetic acid and pH levels. Increased acetic acid concentration affected coleoptile length, mesocotyl length, 1st leaf length and root length significantly. The genotype Bashful was able to produce the longest 1st leaf length at pH 5. The 1st leaf growth of genotype Jahmir varied a little with the pH levels used in this study. Higher pH (pH 7) appeared to minimize acetic acid shock of the seedlings in the process of development.